Release of ranibizumab using a porous poly(dimethylsiloxane) capsule suppressed laser-induced choroidal neovascularization via the transscleral route - Nobuhiro Nagai; Reiko Daigaku; Remi Motoyama; Hirokazu Kaji; Toshiaki Abe (Journal of Materials Science: Materials in Medicine, 2022)
Abstract The administration of anti-vascular endothelial growth factor drugs in the posterior eye segment with sustained release through less invasive methods is a challenge in the treatment of age-related macular disease. We developed a flexible capsule device using porous poly(dimethylsiloxane) (PDMS) that was able to release ranibizumab. The porous PDMS sheet was fabricated by salt-leaching of a micro-sectioned PDMS sheet containing salt microparticles. Observation with scanning electron microscopy revealed that the pore densities could be adjusted by the concentration of salt. The in vitro release study showed that the release rate of fluorescein isothiocyanate-tagged albumin could be adjusted based on the pore density of the porous PDMS sheet. Ranibizumab could be released in a sustained-release manner for 16 weeks. The device was implanted on the sclera; its efficacy in terms of the suppression of laser-induced choroidal neovascularization (CNV) in rats was compared with that of monthly intravitreal injections of ranibizumab. At 8 and 18 weeks after implantation, the CNV area was significantly reduced in rats that received the ranibizumab-releasing device compared with those that received the placebo device. However, although monthly intravitreal injections of ranibizumab reduced CNV for 8 weeks, this reduction was not sustained for 18 weeks. In conclusion, we demonstrated a novel controlled-release device using a porous PDMS sheet that could suppress CNV via a less invasive transscleral route versus intravitreal injections. This device may also reduce the occurrence of side effects associated with frequent intravitreal injections. Graphical Abstract